Altered expression and signal transduction of endothelin‐1 receptors in heritable and idiopathic pulmonary arterial hypertension. Issue 2 (25th October 2012) - Yu, Jun; Taylor, Linda; Wilson, Jamie; Comhair, Suzy; Erzurum, Serpil; Polgar, Peter
Abstract Human pulmonary arterial smooth muscle cells (PASMC) were isolated from elastic pulmonary arteries dissected from lungs of individuals with and without pulmonary arterial hypertension (PAH). Reflecting increased smooth muscle constriction in cells from PAH subject, Ca2+ influx in response to endothelin‐1 (ET‐1) increased in all the PAH PASMC populations relative to the normal donor control cells. The ETA receptor mRNA levels remained unchanged, whereas the ETB receptor mRNA levels decreased in both heritable and idiopathic PAH‐derived PASMC. All the PASMC populations expressed considerably higher ETA compared to ETB receptor number. Both ETA and ETB receptor numbers were reduced in bone morphogenetic protein receptor type II (BMPR2) mutation PAH. ETB receptors showed a particular reduction in number. Phospho‐antibody array analysis of normal and BMPR2 deletion PASMC illustrated ERK and Akt activation to be the most prominent and to be taking place principally through ETB receptors in normal PASMC, but primarily through ETA receptors in PASMC from BMPR2 PAH subjects. Additionally in the PAH cells the total relative ET‐1 signal response was markedly reduced. Western analysis from the BMPR2 PASMC duplicated the array results, whereas PASMC from iPAH subjects showed variability with most samples continuing to signal through ETB. In sum, these results indicate that generally both receptors are reduced in PAH particularly ETB, and that ETB signaling through protein kinases becomes markedly reduced in BMPR2 PASMC, while it continues in IPAH. Importantly, the data suggest that caution must be taken when applying ET‐1 receptor antagonist therapy to PAH patients. J. Cell. Physiol. 228: 322–329, 2013. © 2012 Wiley Periodicals, Inc.